Handbook of research on machine and deep learning applications for cyber security - Ganapathi, Padmavathi, 1964-; Shanmugapriya, D., 1978- (IGI Global, 2020)
"This book explores the use of machine learning and deep learning applications in the areas of cyber security and cyber-attack handling mechanisms"--